THE EFFECTIVENESS OF COMMUNICATION AS A MEDIATING VARIABLE IN IMPROVING THE PERFORMANCE OF LAYER CHICKEN FARMING - Peradnya Dewi, Anak Agung Istri Agung; Suardi, I Dewa Putu Oka; Arisena, Gede Mekse Korri (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
Optimizing chickens as an economic resource to provide maximum income for farmers and their families requires farmers with entrepreneurial competence. To improve the performance of chicken farming businesses, in addition to entrepreneurial competence, farm owners also need enhanced communication skills to navigate the internal and external business environment. This study aims to examine the internal and external environment, entrepreneurial competence, communication, and performance of chicken farm owners in Tabanan Regency and test the effectiveness of communication as a mediating variable between the internal environment, external environment, and entrepreneurial competence on the performance of layer chicken farming businesses in Tabanan Regency. The study was conducted in three villages: Jatiluwih, Senganan, and Babahan in Penebel District, Tabanan Regency. The sample consisted of 30 out of 51 farmers with the criterion of keeping more than 6,000 chickens. The analysis method was divided based on research objectives: the first objective was analyzed using descriptive analysis with class interval calculations, and the second was analyzed using Generalized Structured Component Analysis (GSCA). The results showed that layer chicken farming businesses in Penebel District, Tabanan, exhibited good performance with effective organizational communication and entrepreneurial competence, despite facing internal, external, and research-development challenges. Furthermore, the communication model as a mediating variable is effective in layer chicken farming businesses, indicating that communication plays a crucial role in enhancing performance by effectively mediating changes in the external environment.  Entrepreneurial competence and the internal environment also directly contribute to performance without requiring extensive communication.